SEM Approach for Analysis of Lean Six Sigma Barriers to Electric Vehicle Assembly - Zope, Atul Madhukar; Swami, Raju Kumar; Patil, Atul (Automotive Experiences, 2023)
This study investigates the barriers that the Lean Six Sigma implementation faces during the assembly of electric vehicles. In order to implement lean Six Sigma methodology in electric vehicle assembly processes effectively, it is crucial to identify and analyze the barriers that hinder process improvement. To identify the obstacles and create a conceptual model, a thorough literature review was conducted. Four factors, namely, integration of assembly, inspection, and testing, lack of trained and knowledgeable human resources, external and in-plant battery transportation, and manual assembly and rigid automation, were found to have the potential to affect the lean Six Sigma implementation. Three drivers, namely assembly cost, assembly time, and assembly effort were selected for the study. The model is then tested using the structural equation modeling and the gathered data. The results show a significant relationship between the three drivers and the four barriers of Lean Six Sigma implementation to the electric vehicle assembly.